Effect of aluminium phosphide exposure on kinetic properties of cytochrome oxidase and mitochondrial energy metabolism in rat brain - Dua, Raina; Gill, Kiran D. (Biochimica et biophysica acta, 2004)
This study involves the effect of aluminium phosphide exposure on the kinetic characteristics of cytochrome oxidase and the mitochondrial respiratory chain function in rat brain. Mitochondrial preparations from both control and aluminium phosphide-treated rats demonstrated significant decrease in the maximal activity of cytochrome oxidase (∼50%) when expressed per unit membrane protein and on a turnover number basis (nmol/min/nmol haem a). The results indicated that there was a decrease in the catalytic efficiency of the active oxidase molecules on aluminium phosphide treatment. Arrhenius plot characteristics differ for cytochrome oxidase activity in mitochondria isolated from treated and control rats, in the break point of the biphasic plot which was shifted to a higher temperature. The decreased activity of cytochrome oxidase along with altered NADH and succinic dehydrogenase activities might have contributed towards a significant decline in state 3 and state 4 respiration. These alterations in the electron transport chain complexes in turn affected the ATP synthesis rate adversely in the mitochondria, isolated from treated rats. The data reflect the interaction of aluminium phosphide with redox chain components leading to the impairment of the electron transfer along the respiratory chain.